Meaningful Encounters with the Built Environment as the Basis for Urban Environmental Education - Markus Hilander; Sirpa Tani (Education Sciences, 2022)
As the majority of people in the world now live in cities, it makes sense to question the state of urban environmental education and how it could be developed going forward. In this article, we suggest a way forward based on the essays written by Finnish university students. The students reflected on their relationship with an environment that is meaningful to them. In the essays selected for this case study (n = 25), the built environment of Helsinki—the capital of Finland—and its characteristics are in focus. In this qualitative research, inductive content analysis was used for processing the essays. Many students described the connections between urban nature and built environments, but the results also show that the built environment is especially significant because of its social and cultural aspects. Students described the importance of social bonding and how meeting different sorts of people supports their acceptance of diverse perspectives. Personal experiences and meanings attached to the city, as well as their lack, were mentioned; that is, without these personal bonds, meaningful relations to urban environments cannot be developed. Architecture, aesthetics, and soundscapes were also mentioned. In addition, it was expressed that feeling safe in the built environment is important. In urban environmental education, it is therefore important to pay attention to the social and cultural aspects, too, and not just to the ecological dimension. It is crucial that children and young people have access to the city in order to construct their personal relationships with the built environment.